Present status of biochemical research on the insecticide resistance problem - Agosin, Moises (1963)
In order to provide a rational basis for the development of new insecticides, a thorough understanding of resistance mechanisms is necessary and this presupposes a detailed knowledge of the normal biochemical pathways in insects. The author reviews recent progress in this field, particularly the work on enzymatic detoxication of insecticides which appears to be the most important single factor in the production of resistance. The mechanisms include dehydrochlorination and α-methylenic oxidation (DDT), hydrolysis by phosphatases or carboxyesterases (organophosphorus compounds), and oxidation by microsomal enzyme systems (various classes of insecticides). Much work still needs to be done on the enzyme systems involved, especially in relation to substrate specificity and the effect of enzyme inhibitors that might act as synergists of insecticides.